A Brief Report on the Canadian Chapter: Signing of the MoU between UiTM and the University of Ottawa, Canada. / PM Khas Dr Angeline Ranjethamoney Vijayarajoo - Vijayarajoo, Angeline Ranjethamoney (UiTM Cawangan Negeri Sembilan, 2022)
This memorable and historical journey began on the 15th of August, 2022. The members of the team who left for Canada on government service comprised the following people: Prof Yamin Yasin (our Rector, UiTMCNS) Ts Dr Noorlis Ahmad (Deputy Rector, Academic Affairs, UiTMCNS) Dr Siti Nor Atika Baharin (Liaison Officer, UiTM Global, UiTMCNS) Associate Professor Dr Angeline Ranjethamoney Vijayarajoo (UiTMCNS, APB Seremban,)